CHARACTERISTIC OF ILLEGAL ONLINE LOANS IN INDONESIA - Dwi Tatak Subagiyo; Lorensia Resda Gestora; Sulistiyo Sulistiyo (Indonesia Private Law Review, 2022)
Financial technology is a business that provides financial services by utilizing cutting-edge software and technology. Online loan providers are financial service providers that operate online using information technology. They are well-known for having a simple process and are particularly useful in the current situation, where there is an urgent need, but no funds are available. In less than two years, dozens of financial technology companies have started lending online in Indonesia, far exceeding many people's expectations. However, when applying for credit, many consumers do not consider or care about the legality of online lending institutions. Based on the above description, this research aims to determine the main characteristics of illegal online loans in Indonesia, as well as the legal responsibility of illegal online loan providers to borrowers. The approach used in normative research refers to legal norms, which are laws, regulations, court decisions, and societal norms. The results of the studies showed that characteristics of illegal online loans in Indonesia are often associated with the word illegal because the online loan often has not been or is not authorized by the OJK; this happens because there are requirements that the online loan provider cannot meet. This online loan uses peer-to-peer landings and financial technology (Fintech), authorized in Regulation 77/POJK.01/2016 concerning Information Technology-Based Lending and Borrowing Services governs fintech. Illegal online loan providers can be subject to several sanctions, including; administrative sanctions, criminal sanctions, and civil sanctions.